(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article describes three types of communicative behavior of individuals during the stage of development of interpersonal conflict. It was found, that the first type is caused by participants’ understanding of the transition from latent conflict state into an open confrontation, the second – their knowledge of escalation of the conflict, and the third – is recognized by the presence of the phase peak.